Trends and variability of temperature extremes in the tropical Western Pacific. (22nd November 2013) - Whan, K.; Alexander, L. V.; Imielska, A.; McGree, S.; Jones, D.; Ene, E.; Finaulahi, S.; Inape, K.; Jacklick, L.; Kumar, R.; Laurent, V.; Malala, H.; et al.
ABSTRACT A new high‐quality daily and monthly temperature station dataset was prepared for the tropical Western Pacific through a quality control and homogenization process. The homogeneity of 46 temperature stations, collected at a workshop conducted as part of the Pacific‐Australia Climate Change Science and Adaptation Planning program, was assessed and the non‐climatic step changes were removed. Here we present trends in mean and extreme temperature for the Western Pacific, covering an extended time period and larger geographical area compared with previous analyses. We discuss five main conclusions: (1) There is a significant warming trend in annual mean temperature over the past 50 years (1961–2011), of between 0.05 and 0.34 °C per decade. (2) Significant and spatially homogeneous warming trends are evident at the station level over 1961–2011 for the warm and cool extremes of both maximum and minimum temperatures. (3) Sub‐regional trends, over the period 1951–2011, are spatially coherent, with the largest warming trends in the hottest day and night of the year and the coolest night of the year. (4) This analysis highlights the role of decadal variability in the number of days exceeding extreme temperature thresholds, with the upper (lower) tails of the distribution warming more (less) in recent decades. (5) We show that strong relationships exist between local and remote sea‐surface temperature anomalies and all indices of extreme temperature, particularly with minimum temperature extremes.